Narratives of Resistance in Everyday Lives and the Covid Crisis (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Narratives of Resistance in Everyday Lives and the COVID-19 Crisis brings together 21 global scholars of political narratives across five continents focused on the impact of the COVID-19 events on political societies. From Seoul to Stockholm the wave of sudden and dramatic changes in work, social life, political order, and bodily regulation affected pre-existing social forces and relations. This collection of chapters asks what changed, and with what degree of permanence? It explores which master/grand narratives retained their coherence, and which were called into question. Having established radical new protocols of social distancing, remote working and learning, masking, isolation, and quarantining, the reprint reveals the political and social possibilities that came to prominence and which ones were occluded. It questions what the prospects for a post-COVID-19 order might be. Most importantly, it asks, what happened to political agency, community activism, resistance, protest, and mobilization throughout the pandemic? Three general themes emerge across the contributions to this volume: first, the deep complexities of political resistance throughout the pandemic; second, the emergence of progressive conceptions of alternative futures, conditioned by responding to the exigencies of the pandemic; and, finally, notwithstanding these developments, the persistent reproduction of “business as usual”.